2023
DOI: 10.1101/2023.04.07.534593
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthetically mannosylated antigens induce antigen-specific humoral tolerance and reduce anti-drug antibody responses to immunogenic biologics

Abstract: Immunogenic biologics trigger an anti-drug antibody (ADA) response in patients, which reduces efficacy and increases adverse reactions. Our laboratory has previously shown that targeting protein antigen to the liver microenvironment can reduce antigen-specific T cell responses; herein, we present a strategy to increase delivery of otherwise immunogenic biologics to the liver via conjugation to a synthetic mannose polymer (p(Man)). This delivery leads to reduced antigen-specific T follicular helper cell and B c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…Wallace et al described the synthesis of a glycopolymer called p(Man), which effectively targeted the liver and reduced antigen-specific cellular and humoral responses to various immunogenic proteins 21 . Here, we conjugated the polymer to BLG using a self-immolative DBCO linker ( Figure 1A, Figure S1, S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Wallace et al described the synthesis of a glycopolymer called p(Man), which effectively targeted the liver and reduced antigen-specific cellular and humoral responses to various immunogenic proteins 21 . Here, we conjugated the polymer to BLG using a self-immolative DBCO linker ( Figure 1A, Figure S1, S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that glycosylation-modified conjugated antigens are successful at inducing both cellular and humoral tolerance through liver targeting, preventing the onset of autoimmune disease 18 and ADA responses 22 . However, s.c. administration could be clinically preferable for preventing food allergy in infants and children and may present fewer systemic safety concerns if administered to patients with existing food allergies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations